Better Reproductive Health for Poor Women in South Asia - Chatterjee, Meera (World Bank, 2012)
The overall purpose of this review is to bring attention to the opportunities that five countries in the region - Bangladesh, India, Nepal Pakistan and Sri Lanka have to strengthen and expand interventions to improve the reproductive health of poor women. The report's specific objectives are: 1) to provide an accurate picture of the current status of women's reproductive health and describe the use of reproductive health services and barriers to use; 2) to identify individual and household characteristics that affect reproductive health status and use of services; 3) to develop a simple and effective approach to decentralized health planning that can be used widely in each of the five countries to improve health service delivery and outcomes locally; and 4) to strengthen the case for investing in poor women's reproductive health by demonstrating the links between poverty, inequality and reproductive health. The review puts forth the following recommendations for reforms for reproductive health: to increase the supply of reproductive health services to poor women and adolescents by specifically targeting the poorest areas and households; to enhance demand among the poor for key services using BCC and demand-side financing; to integrate reproductive health services through a client-centered approach and strengthen weak services using specific relevant approaches; and to improve the reach, quality and status of women providers by better training, deployment and support are the 'frontline' improvements required for better reproductive health among poor women in South Asia.